Rare or overlooked? The distribution of Hairy Jointgrass in north coast New South Wales, Australia, and implications for its conservation status - White, L.; Catterall, C.; Tomlinson, Sean; Taffs, K. (ELSEVIER GMBH, 2020)
Efficient threatened species prioritisation and management is critical to the overall success of biodiversity conservation. Insufficient species information can make it challenging to accurately assess a species’ extinction risk and develop appropriate management strategies. In this study we undertook field surveys and spatial data analysis to better understand the habitat and distribution of the threatened annual grass Arthraxon hispidus (Thunb.) Makino (Hairy Jointgrass) within its north coast New South Wales range. We developed and tested a high-resolution maximum entropy (Maxent) model, using field survey population mapping and freely available spatial data (e.g. soil, topography, foliage cover, hydrology) to identify its landscape distribution drivers, to predict its suitable habitat areas and to estimate its abundance. The model indicated that A. hispidus habitat occurs in non-woody vegetation in areas of high topographic wetness and persistent moisture, particularly in and around drainage lines or on south-facing slopes. We found that A. hispidus appears to be much more widespread than previously known, with high rates of occurrence at predicted but previously unsurveyed sites, and approximately 15 % of the study area projected to be suitable habitat for the species. We estimated that the extent of occurrence and area of occupancy of the species exceeded vulnerable species listing criteria thresholds within IUCN guidelines. This study demonstrates how species distribution modelling can add to existing resources to provide cost-effective data to inform and streamline conservation planning.